The policy of evaluation of brazilian basic education: ideb and space in analysis - Moreira, Atales Samara Sampaio; Dias, José Nailson Alves; Miranda, Thaynara Ingride Araújo; Sousa, Elizangela Gomes de; Mota, José Wilton Albuquerque; Paula, Alisson Slider do Nascimento de (Revista Hipótese, 2018)
The objective was to discuss the essential elements of the logic of the Brazilian educational evaluation, especially the evaluation policies, namely Ideb and SPAECE. This is a bibliographical and documentary study. Ideb together with SPAECE comply with the guidelines of international organizations. The official discourse points to an improvement in the supposed "quality" of education, however, Brazil is still one of the countries with the greatest educational inequality that is tied to income inequality and equity.
Keywords: Ideb; SPAECE; Education